Determinants of Profitability of Licensed Commercial Banks in Sri Lanka. - Kengatharan, L.; Sivajini, A. (South Eastern University of Sri Lanka, 2017)
Since banks play an important role in the economy, this study attempts to examine the determinants of profitability of licensed commercial banks in Sri Lanka over the 10 years period from 2006 to 2015. The analysis is based on a sample of 09 licensed commercial banks in Sri Lanka. Descriptive and inferential statistics have been used to examine the determinants of profitability of the banks. Return on Assets (ROA) and Return on equity (ROE) have been taken as the profitability measures, bank specific characteristics such as bank capital adequacy, bank operational cost efficiency, bank nonperforming loans, bank liquidity and bank size as well as macroeconomic variables such as economic growth rate and interest rate have been taken as explanatory variables. Results of the study indicate that bank specific factors such as operational cost efficiency and nonperforming loans have a negative impact on profitability while capital adequacy has a positive impact on profitability. Within the macroeconomic variables, economic growth rate has a positive impact on profitability while interest rate shows that there is no significant impact on profitability as measured according to ROA, while according to ROE nonperforming loans ratio significantly negatively impact on ROE and rest of the variables exhibit insignificant impact on ROE.
Keywords: Operating cost efficiency; Non-performing loans; Capital adequacy ratio; Economic growth rate; ROA; ROE